'I Would Really Like to Go Where You Go': Rethinking Migration Decision‐Making Among Educated Tied Movers. Issue 2 (6th October 2015) - Clerge, Orly; Sanchez‐Soto, Gabriela; Song, Jing; Luke, Nancy
Abstract: This paper studies 'tied mover' men and women who are the partners of graduate students. We use qualitative data to explore the relocation decision‐making process of married and unmarried partners. We find that, while many partners have educational and career aspirations of their own, the maintenance of the relationship is a strong priority that dictates how and when a tied move occurs. Furthermore, the decision‐making process is varied and depends on the stage of the relationship. Tied movers at earlier points in their relationships often make independent decisions to join their graduate student partners after the student has already initiated the move. Some of those in more mature relationships follow a traditional mover–follower model, while others participate in joint decision‐making about their destination. Finally, we find that over one‐third of the tied movers are male, reflecting both increases in women's migration for graduate school and men's openness to 'following' career‐oriented partners. This paper contributes to the study of family migration by developing a model focusing on individual and collective non‐economic determinants of couples' decisions to migrate for skill development. Copyright © 2015 John Wiley & Sons, Ltd.